The Three‐Dimensional Light Field Within Sea Ice Ridges. Issue 11 (7th June 2021) - Katlein, Christian; Langelier, Jean‐Philippe; Ouellet, Alexandre; Lévesque‐Desrosiers, Félix; Hisette, Quentin; Lange, Benjamin A.; Lambert‐Girard, Simon; Babin, Marcel; Thibault, Simon
Abstract: Sea ice pressure ridges have been recognized as important locations for both physical and biological processes. Thus, understanding the associated light‐field is crucial, but their complex structure and internal geometry render them hard to study by field methods. To calculate the in‐ and under‐ridge light field, we combined output from an ice mechanical model with a Monte‐Carlo ray tracing simulation. This results in realistic light fields showing that light levels within the ridge itself are significantly higher than under the surrounding level ice. Light guided through ridge cavities and scattering in between ridge blocks also results in a more isotropic ridge‐internal light field. While the true variability of light transmittance through a ridge can only be represented in ray tracing models, we show that simple parameterizations based on ice thickness and macro‐porosity allow accurate estimation of mean light levels available for photosynthesis underneath ridges in field studies and large‐scale models. Plain Language Summary: When two slabs of sea ice collide, they can break and form pressure ridges by piling up loose ice blocks over each other. The light environment within these ridges is very complicated, but also crucial for their characteristics as habitat for the sea ice ecosystem. We calculate the light field within and underneath such a pressure ridge by tracing the path of many individual photons through the ridge geometry. Our results show that light levels within the ridge can be higher than in the adjacent undeformed ice. We suggest simple equations that can be used in large scale models to estimate the light intensity underneath the pressure ridge based on ice geometry data that can be obtained in the field. Key Points: We computed the full three‐dimensional light field inside and underneath a pressure ridge Scalar irradiance is enhanced within the ridge compared to under level ice Simple parameterizations can capture key aspects of the ridge light field, for example, for habitat characterization and large scale models